Astronomy - Amato, Carol; Moros, Steven (New York : Smithmark, 1992)
Explores discoveries about the universe and discusses landing on the Moon, placing a telescope into space, and phenomena about which we are still learning.
Includes bibliographical references and index.
School Library Journal
3-6
Keywords: Astronomy -- Juvenile literature; Astronomy; Astronomy